PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PRODUK PAKAIAN PADA TOKO RABBANI PEKANBARU - Mardiah Dasra; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much products quality and promotion to consumer buying interest. Sampels in this study were taken as many as 100 respondens and techniques used accidental sampling approach. The data in this study using survey method through questionnares filled by consumers. Data were obtained by using simple regression analysis dan multiple regression analysis. The result of this study show that products quality has a significant impact on consumer buying interest. Promotion has a significant impact on consumer buying interest. And then simultaneously products quality and promotion have a significant impact on consumer buying interest. Subsequent research is suggested to use other methods in researcing consumer buying interest, for example through in-depth interviews of respondents.Keywords: Product Quality, Promotion, And Consumer Buying Interest